Ta’tsir Istikhdam Thariqah al-Sam’iyah al-Syafawiyah wa Thariqah al-Mubasyarah ‘ala Nataij Ta’allum Maharah al-Kalam bi Madrasah al-Tsanawiyah (Dirasah Muqaranah) - Mustar, Mustar; Yusraini, Yusraini; Qodri, Muhammad; Umasugi, Muhammad Kumaini; Pertiwi, Nadia Indah (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This article aimed to compare students' Arabic language learning outcomes of speaking skills due to the use of Audio-Lingual and direct methods. The author compared the results of the two methods to see their impacts on students’ Arabic speaking skills at Madrasah Aliyah Nurul Iman Ulu Gedong. This referred to comparative quantitative research with the type of experimental research (Post-Test-Only Control). The results of this research showed that: 1). Students' Arabic speaking skills using the Audio-Lingual method obtained the highest score of 95 and the lowest score of 53 with an average of 73.79. 2). Students’ Arabic speaking skills using the Direct method obtained the highest score of 66 and the lowest score of 28 with an average of 47.71. Thus, students’ Arabic speaking skills taught using the Audio-lingual method were higher than those taught using the direct method. 3). Based on the results of hypothesis testing using the paired sample t-test, there was a significant difference in learning outcomes of students' Arabic speaking skills as getting taught by using Audio-lingual and the Direct methods.